2012
DOI: 10.1111/j.1364-3703.2012.2011.00783.x
|View full text |Cite
|
Sign up to set email alerts
|

The Top 10 fungal pathogens in molecular plant pathology

Abstract: The aim of this review was to survey all fungal pathologists with an association with the journal Molecular Plant Pathology and ask them to nominate which fungal pathogens they would place in a 'Top 10' based on scientific/economic importance. The survey generated 495 votes from the international community, and resulted in the generation of a Top 10 fungal plant pathogen list for Molecular Plant Pathology. The Top 10 list includes, in rank order, (1) Magnaporthe oryzae; (2) Botrytis cinerea; (3) Puccinia spp.;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
253
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(262 citation statements)
references
References 158 publications
0
253
0
9
Order By: Relevance
“…FAO (2011) mentioned that the percentage of losses of fruits and vegetables during post-harvest handling, storage and packaging 34% in South and Southwest Asia, 30% in Latin America, Central Asia and North Africa, 10% in industrialized countries of Asia, 7% in Europe and 6% in North America and Oceania. In the present study, the most important species of fungi were found in the genus Penicillium, Botrytis, Monilinia, Rhizopus, Alternaria, Aspergillus, Fusarium, Mucor, Gloeosporium and Colletotichum represent the pathogens responsible for the most important postharvest disease (Dean et al, 2012;Liu et al, 2013).…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…FAO (2011) mentioned that the percentage of losses of fruits and vegetables during post-harvest handling, storage and packaging 34% in South and Southwest Asia, 30% in Latin America, Central Asia and North Africa, 10% in industrialized countries of Asia, 7% in Europe and 6% in North America and Oceania. In the present study, the most important species of fungi were found in the genus Penicillium, Botrytis, Monilinia, Rhizopus, Alternaria, Aspergillus, Fusarium, Mucor, Gloeosporium and Colletotichum represent the pathogens responsible for the most important postharvest disease (Dean et al, 2012;Liu et al, 2013).…”
Section: Introductionmentioning
confidence: 59%
“…FAO (2011) mencionó que el porcentaje de pérdidas de frutos y vegetales durante el manejo poscosecha, almacenamiento y empaque 34% en el Sur y Suroeste de Asia, 30% en América Latina, Asia Central y Norte de África, 10% en países industrializados de Asia, 7% en Europa y 6% en Norteamérica y Oceanía. Especies de hongos dentro de los géneros Penicillium, Botrytis, Monilinia, Rhizopus, Alternaria, Aspergillus, Fusarium, Mucor, Gloeosporium y Colletotichum, representan los patógenos responsables de las enfermedades poscosecha más importantes (Dean et al, 2012;Liu et al, 2013).…”
Section: Introductionunclassified
“…Rice blast (caused by the fungal pathogen Magnaporthe oryzae) and bacterial blight (caused by the bacterial pathogen Xanthomonas oryzae pv. oryzae) are the most devastating rice diseases (119) and are among the 10 most important fungal and bacterial diseases in plants (32,95). Owing to their scientific and economic importance, both pathosystems have been the focus of concentrated study over the past two decades, and they are now advanced molecular models for plant fungal and bacterial diseases.…”
Section: Important Rice Diseasesmentioning
confidence: 99%
“…Poznane dotychczas białka efektorowe grzybów bio-i hemibiotroficznych pochodzą w większości z Magnaporthe oryzae wywołującego zarazę (plamicę) ryżu, z Leptosphaeria maculans powodującego zgniliznę kapustnych, z Melamspora linii infekującego len oraz z mączniaka prawdziwego zbóż i traw (Blumeria graminis), a więc gatunków, które na liście 10 najgroźniejszych grzybów patogennych zajmują miejsca czołowe [29]. Warto też zauważyć, że spośród 17 analizowanych białek efektorowych grzybów wprowadzanych do rośliny, około 61% pozostaje w cytoplazmie, 28% wnika do jądra, a 11% migruje do błon [26].…”
Section: Białka Efektorowe Fitopatogenów Ingerujące W Reakcje Odpornounclassified